A structural design for semi-rigid base asphalt pavement based on modulus optimization. (4th October 2021) - Lv, Songtao; Yuan, Jiang; Peng, Xinghai; Zhang, Naitian; Liu, Hongfu; Luo, Xinzi
Highlights: The mechanical response between the field measured and the designed modulus was compared. The optimization for modulus combinations of pavement structural was proposed. The fatigue properties of material and structure were unified. Abstract: The early damage of the semi-rigid base asphalt pavement is related to the pavement structure modulus's unreasonable matching. In this study, three typical pavement structures were selected to analyze the pavement structures' influence on the pavement service life. A three-dimensional finite element pavement structure model was established. The independent variables are subgrade modulus, base course modulus, and subbase modulus. The deflection, the bottom tensile stress, and maximum shear stress were chosen as the evaluation indexes. The effect of the modulus on the mechanical response of the pavement structure was analyzed. The optimal modulus combination of the pavement structure was determined through multi-factor range analysis. The mechanical response and fatigue life before and after the optimization pavement structure were compared. The results showed that the field measured modulus of Structure 1 and 2 was higher than the design modulus. Moreover, while the modulus of base course and subbase course was increased, the deflection gradually reduced. The base course's bottom tensile stress and the subbase were increased, and the maximum shear stress was basically unchanged. After the modulus combination optimized pavement structure, the mechanical response was significantly reduced. The fatigue life based on the deflection and bottom tensile stress, and the laboratory normalized fatigue equation were significantly increased. By the combination of fatigue performance of pavement materials and pavement structure, it was possible to provide an effective optimization method for the design of semi-rigid base asphalt pavement in this research work.